Оцінка якості життя у осіб з легкою розумовою відсталістю підліткового віку - Підлубний, Віталій Леонідович; Чабанюк, Сергій Олександрович; Pidlubnyi, V.; Chabanyuk, S.; Подлубный, В. Л.; Чабанюк, С. А. (My University, 2021)
Актуальність. Інтегральним показником фізичного, психічного та соціального функціонування у медицині є суб’єктивна оцінка хворим якості його життя. Цей показник знаходиться в прямій залежності до спроможності індивіда до психічної адаптації зовнішніх та внутрішніх умов, змінених під впливом захворювання. Саме аналізу впливу легкої розумової відсталості підліткового віку на рівень якості життя та соціального функціонування хворих присвячено дане дослідження. Мета дослідження. Визначити рівні якості життя та соціального функціонування в осіб з легкою розумовою відсталістю підліткового віку, як критерії оцінки стану хворих. Relevance. An integral indicator of physical, mental and social functioning in medicine is the patient’s subjective assessment of the quality of his life. This indicator is in direct proportion to the ability. The individual to mental adaptation to external and internal conditions, changed under the influence of the disease. This study is devoted to the analysis of the influence of mild mental retardation of adolescence on the level of quality of life and social functioning of patients. Purpose of the study. To determine the levels of quality of life and social functioning in persons with mild mental retardation of adolescence, as criteria for assessing the condition of patients. Materials and research methods. On the basis of the Kryvyi Rih neuropsychiatric dispensary, subject to informed consent, a two-stage study was carried out, in which 154 patients born in 2003- 2008 were examined, who were under the dispensary observation of an adolescent psychiatrist upon reaching the age of 15. In the course of the study, clinical-epidemiological, clinical-psychopathological, psychodiagnostic and statistical methods were used. Актуальность. Интегральным показателем физического, психического и социального функционирования в медицине есть субъективная оценка больным качества его жизни. Этот показатель находится в прямой зависимости cо способностью индивида к психической адаптации к внешним и внутренним условиям, измененных под влиянием заболевания. Именно анализу влияния легкой умственной отсталости подросткового возраста на уровень качества жизни и социального функционирования больных посвящено данное исследование. Цель исследования. Определить уровни качества жизни и социального функционирования у лиц с легкой умственной отсталостью подросткового возраста, в качестве критериев оценки состояния больных.
Assessment of the quality of life in persons with slight mental disability in adolescence
Оценка качества жизни у лиц с легкой умственной отсталостью подросткового возраста
Keywords: розумова відсталість; соціальна адаптація; якість життя; реабілітація; психіатрія; mental retardation; social adaptation; quality of life; rehabilitation; psychiatry; умственная отсталость; социальная адаптация; качество жизни; реабилитация; психиатрия